Path Analysis: Effect of Gestational Factors, Psychosocial Factors, and Antenatal Class Program on Toddler Growth - Gita Ayu Indria; Bhisma Murti; Yulia Lanti Retno Dewi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2016)
Background: According to David Barker